Meridians of Salt
XIV, 541 p. 191 illus., 150 illus. in color.
Keywords: This book explores the relationship between salt (sodium chloride) and the development of human societies from a cross-cultural and global perspective. Although it is not possible to discuss the importance of salt to all ancient and modern societies, the geographically and temporally diverse examples highlighted here are used to examine a series of related topics critical to understanding the economic, political, social, and religious impacts of salt through space and time. These topics include, among others, the techniques used to produce salt, the individuals responsible for its production, its cultural uses and applications, its role in cross-cultural exchange, and the impact of its circumscribed distribution on settlement patterns and developing complexity. In exploring these topics, the chapter authors rely on archaeological data to craft their interpretations, however, as salt itself is largely invisible in the archaeological record, other avenues of investigation such as ethnoarchaeology, ethnohistory, and experimental archaeology are necessary to gain a more complete understanding of this mineral’s influence on the development of human cultures. Each chapter includes a summary of seminal research within a particular geographic region along with a discussion of recent or on-going projects from that area. This volume is intended for a professional audience, but university students and graduates and readers with an interest in anthropology, archaeology, ethnoarchaeology, or history will find the chapters comprehensible and informative.